The Impact of Group Size on Students’ Reading Fluency in Kindergarten - Benvenuto, Sara (My University, 2019)
The purpose of this study was to determine if a smaller group size would effect the reading achievement of kindergarten students. The participants in this study were enrolled in a Baltimore County Public School during the school year of 2018-2019. The large group consisted of 7 on-level students and the smaller group included 3 on-grade level students. The instruction took place for 20 minutes each week. During these lessons students read from the leveled books from McGraw-Hill Education Wonders Curriculum; they were taught reading strategies and used identical fluency activities. After the 10-week research study the teacher used the Fountas and Pinnell (2011) Benchmark Assessment System to measure their reading achievement. The null hypothesis was that there would be no difference in the reading fluency results of the students who participated in the two groups of students. The results had insufficient evidence, rejecting the null hypothesis. Therefore, the size of the group for reading instruction does not affect the reading levels of students for groups of 3 and 7 students.
Keywords: guided reading; small groups; group size; reading fluency; Education -- Research papers (Graduate).